2022
DOI: 10.1002/hsr2.534
|View full text |Cite
|
Sign up to set email alerts
|

A path causal model in the association between self‐efficacy and self‐care with quality of life in patients with type 2 diabetes: An application of the structural equation model

Abstract: Background and Aims The simultaneous role of self‐care and self‐efficacy in improving the quality of life (QoL) of diabetic patients has been less considered in previous studies. This study was aimed to investigate the path association between self‐care and self‐efficacy with QoL using the structural equation model (SEM). Methods This cross‐sectional study was conducted with 496 individuals of type 2 diabetic patients aged 35–75 years that were selected consequently fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Twenty-two studies ( n = 5,005) ( 44 46 , 49 , 51 , 52 , 56 , 68 , 70 , 72 , 74 , 79 , 81 , 82 , 84 , 85 , 91 , 95 , 98 – 100 , 104 ) evaluated the relationship between empowerment-related constructs and general QoL in patients with T2DM. Specific patient empowerment scales were used in six studies ( 44 46 , 49 , 51 , 52 ) while self-efficacy was used in the remaining sixteen studies ( 56 , 68 , 70 , 72 , 74 , 79 , 81 , 82 , 84 , 85 , 91 , 95 , 98 – 100 , 104 ). One study ( 44 ) used ANOVA to quantify this association and was not included in the MA.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies ( n = 5,005) ( 44 46 , 49 , 51 , 52 , 56 , 68 , 70 , 72 , 74 , 79 , 81 , 82 , 84 , 85 , 91 , 95 , 98 – 100 , 104 ) evaluated the relationship between empowerment-related constructs and general QoL in patients with T2DM. Specific patient empowerment scales were used in six studies ( 44 46 , 49 , 51 , 52 ) while self-efficacy was used in the remaining sixteen studies ( 56 , 68 , 70 , 72 , 74 , 79 , 81 , 82 , 84 , 85 , 91 , 95 , 98 – 100 , 104 ). One study ( 44 ) used ANOVA to quantify this association and was not included in the MA.…”
Section: Resultsmentioning
confidence: 99%
“… 54 Improving self-efficacy among patients with type 2 diabetes has a positive direct impact on both self-care and quality of life. 55 Therefore, measures to improve self-efficacy among patients with type 2 diabetes should be adopted. Previous studies demonstrated that peer support and mobile apps for diabetes management can help people with type 2 diabetes improve their self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐efficacy is a psychological construct in managing chronic conditions (Xie et al, 2020), which directly influences dedication to sustaining health behaviors and improving health outcomes (Bandura, 2018). Higher self‐efficacy leads to better adherence to self‐care (Fereydouni et al, 2022), improved DSM (Hurst et al, 2020), and reduced diabetes complications (C. Tan, Cheng, et al, 2020). However, DSM requires lifelong commitment and motivation (Speight et al, 2020), coping with new and undesirable situations, and adapting to these situations physiologically and psychologically (Fidan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%